2001
DOI: 10.2214/ajr.177.6.1771411
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Harmonic Imaging for the Diagnosis of Vesicoureteral Reflux in Pediatric Patients

Abstract: Visualization of the urinary tract and detection of ultrasound contrast media is significantly improved by the use of the harmonic imaging modalities. When both fundamental and harmonic imaging options are available, we recommend harmonic imaging for contrast-enhanced sonographic diagnosis of vesicoureteral reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 10 publications
1
28
0
4
Order By: Relevance
“…Performing VUS with fundamental US at higher contrast doses might have improved its detection rate. On the other hand, a recent study by Darge et al using the higher standard contrast dose of 10% of the bladder volume confirms our results: the authors found reflux that was only visible on PIUS and not on fundamental US in 8 KUU (29%) of 27 KKU where reflux and image quality was improved by PIUS in all cases [25].…”
Section: Discussionsupporting
confidence: 91%
“…Performing VUS with fundamental US at higher contrast doses might have improved its detection rate. On the other hand, a recent study by Darge et al using the higher standard contrast dose of 10% of the bladder volume confirms our results: the authors found reflux that was only visible on PIUS and not on fundamental US in 8 KUU (29%) of 27 KKU where reflux and image quality was improved by PIUS in all cases [25].…”
Section: Discussionsupporting
confidence: 91%
“…With newest technical refinements, such as contrast harmonic imaging or stimulated acoustic emission, with inclusion of the bladder into the scanning protocol, even low-degree VUR has become reliably detectable [99]. Now EECS offers a non-ionising method for VUR evaluation, at the cost of little functional information, less accurate grading, equipment and operator dependency, and insufficient anatomical evaluation of the ureters, the urethra or some diverticula (e.g.…”
Section: Other Methods For Vur Evaluationmentioning
confidence: 99%
“…Cyclic filling can be performed; however, this makes the procedure expensive, as new contrast has to be prepared. Contrast harmonic imaging improves contrast delineation and depiction and thus reduces the necessary amount of agent need [99].…”
Section: How To Perform Cystographymentioning
confidence: 99%
“…4 ), and various bladder fi lling techniques for direct vesicoureteral refl ux visualization after bladder catheterization. Air, saline (shaken), and -most commonly -sonographic contrast agents have been successfully used for refl ux cystosonography; particularly, contrast -enhanced voiding urosonography (ce-VUS) has been established as a reliable and nonirradiating imaging modality for vesicoureteral refl ux detection, with an even higher sensitivity for vesicoureteral refl ux detection than conventional fl uoroscopic VCUG, particularly using modern agent detection techniques (Bosio 1998 ;Darge et al 1999Darge et al , 2001Kenda et al 2000 ;Berrocal et al 2001 ;Riccabona et al 2003a , b ;Darge et al 2005 ). Any contrast material detected in the ureter or the renal cavities indicates vesicoureteral refl ux (Fig.…”
Section: Ultrasoundmentioning
confidence: 99%